Improved daylight-induced photocatalytic performance and suppressed photocorrosion of N-doped ZnO decorated with carbon quantum dots1. Issue 57 (25th June 2015) - Muthulingam, S.; Bae, Kang Bin; Khan, Rizwan; Lee, In-Hwan; Uthirakumar, Periyayya
<x xml:space="preserve">Abstract</x> An N-doped ZnO photocatalyst decorated with carbon quantum dots and active under irradiation with daylight was developed for the degradation of dyes in industrial wastewaters.